Optical communication based V2V for vehicle platooning - Jiajun Zhang; Ran Zhan; Yuhao Wang; Xiaobo Qu (Green Energy and Intelligent Transportation, 2025)
Vehicle platooning offers significant advantages, including improved fuel economy, reduced congestion and collisions, and decreased air resistance, owing to synchronized acceleration and braking within the platoon. In a vehicle platoon, vehicle-to-vehicle (V2V) communication plays a pivotal role in facilitating information transmission between leading vehicle (L+V) and following vehicle (FV). However, existing V2V communication solutions, such as Dedicated Short-Range Communications (DSRC), Cellular Vehicle-to-Everything (C–V2X), and Visible Light Communication (VLC), face limitations, including high costs, infrastructural and network demands, and privacy concerns. To overcome these challenges, our research introduces a novel vision-based, network-independent information transmission approach. This method can be used as a complement to traditional V2V methods, especially under poor network conditions or potential attacks from adversaries. Simulations and experiments reveal that our approach can facilitate vehicle-to-vehicle information transmission even when network conditions are completely absent, thereby enhancing driving safety. This is achieved through the use of an LED matrix embedded in the leading vehicle′s taillight for communication. This innovative approach holds promise as a solution to the challenges associated with conventional V2V communication methods.